I Listen, Therefore I Am: An Asian American Approach to Post-Materialist Living - McDaniel, Jay (Dialog, 2010)
Consumerism is a cultural atmosphere that permeates societies when they are saturated with market-driven values at the expense of social values. It prioritizes personal needs over the common good and reduces even religion to a “brand” that people wear like an emblem. It simultaneously approaches the world itself as a resource to be managed, forgetful of the fact that all living beings are songs and stories worth hearing. As Christianity becomes a post-western religion, opportunities emerge for Christians to develop cross-cultural poetics that are conducive to post-materialist ways of living in the world. Poetics are not theologies, but rather outlooks on life or, perhaps more appropriately, ways of listening to the voices of people and other living beings. The purpose of this essay is to propose one such Asian American theology that can be a commitment to deep listening: that is, to dwelling musically in the world. This manner of dwelling can recognize that even the heart of the universe—even God—is a listening presence at the heart of the universe.